Integrated Traditional Chinese and Western Medicine Treatment of Oral Squamous Cell Carcinoma - Hualin He (International Journal of Biology and Life Sciences, 2026)
The most prevalent of all oral cancers is the oral squamous cell carcinoma (OSCC), and it constitutes over 90 percent of this group. Its occurrence has only been on the rise in recent years, mostly because of the high use of betel nut, tobacco, and alcohol. The traditional treatment procedures mostly consist of approaches relying on Western medicine, as surgery is the dominant form of treatment, and this is complemented by chemotherapy and/or radiotherapy. Though these methods have short-term ability to treat tumors, they fail to treat them effectively due to drug resistance and other side effects, including oral mucositis and bone marrow suppression, which decreases patient therapeutic compliance. Further, the special anatomical position of the mouth cavity, along with the high aesthetic expectations of the face, leads to the fact that inappropriate surgery can become a major physical and psychological liability to the patients. Traditional Chinese medicine (TCM) focuses on holistic control and differentiation of syndromes. The multi-component, multi-target, and multi-pathway action of Chinese herbal medicaments is marked by characteristics and has proven distinct benefits in the case of alleviating toxicity on chemotherapy/radiotherapy, improving immune functions, and slowing down tumor growth. This review is a summary of the recent research to discuss the mechanisms of Chinese herbal medicine in treating OSCC and discuss the clinical feasibility and prospects of integrated traditional Chinese and Western medicine, which may aim to provide theoretical support and reference directions on the clinical management of OSCC.